2006
DOI: 10.1089/thy.2006.16.447
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HLA-DRB1 Alleles with CTLA-4 in the Predisposition to Graves' Disease: The Impact of DRB1*07

Abstract: Our results stress the importance of complex gene interactions in the multigene predisposition to GD. The interactions between two predisposing loci, DRB1 and CTLA-4, are exerted rather by DRB1*07 than DRB1*03 allele: CTLA-4 acts via switching off the protective DRB1*07 influence, whereas the effect of DRB1*03 is independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…In the present study we have shown that the frequency of the polymorphic GG genotype at position 49 of exon 1 of the CTLA-4 gene is significantly increased in Polish HT children compared to the control group. These results confirm the association between A/G49 CTLA-4 gene polymorphism and AITD reported previously in the Polish population by other authors [25,26]. In the present study the mean concentration of anti-Tg Abs was significantly higher in sera from GG homozygous patients compared to wild AA homozygotes.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study we have shown that the frequency of the polymorphic GG genotype at position 49 of exon 1 of the CTLA-4 gene is significantly increased in Polish HT children compared to the control group. These results confirm the association between A/G49 CTLA-4 gene polymorphism and AITD reported previously in the Polish population by other authors [25,26]. In the present study the mean concentration of anti-Tg Abs was significantly higher in sera from GG homozygous patients compared to wild AA homozygotes.…”
Section: Discussionsupporting
confidence: 93%
“…HLA-DRB1 typing was performed using sequence-specific oligonucleotides (SSO, Innolipa HLA-DRB1, Innogenetics, Gent, Belgium) and sequence-specific primers (MSSP Class II DRB Only, One Lambda, Dynal All Set SSP DR test, Dynal Biotech, Oslo, Norway) (Kula 2006) [25] in the Gliwice study, and by Dynal All Set SSP Dr test (Dynal Biotech, Bromborough, Wirral, UK) in the Warsaw study (Bednarczuk 2004) [26]. CTLA-4 and PTPN22 were analysed by PCF-RFLP methods, as previously described (Jurecka-Lubieniecka 2013 [27], Kula 2006 [25], Bednarczuk 2003 [28], Skórka 2005 [29]) [Table 1]. In the Gliwice study PCR was performed with 0.5 units Hot Star Taq polymerase (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…At present it is not clear which locus is responsible for the observed association. Out of the three most frequently studied genes encoded on this haplotype DQB1 *02 can be excluded as it is commonly found on haplotypes encoding DRB1 *07 which appear to protect from GD [23-25]. Conversely, the relative importance of DQA1 *05 and/or DRB1 *03 is under discussion.…”
Section: Genes Predisposing To Gdmentioning
confidence: 99%